Mapping Trends and Hotspots Regarding the Use of Lung Ultrasound in the Field of Anesthesiology: A Bibliometric Analysis of Global Research - Jiang W; Kang K; Zhou X; Chen X; Yu H; Zhang X (Medical Devices: Evidence and Research)
Wencai Jiang,1 Kang Kang,2 Xinyu Zhou,1 Xuemeng Chen,1 Hai Yu,2,* Xianjie Zhang1,* 1Department of Anesthesiology, Deyang People’s Hospital, Deyang, 618000, People’s Republic of China; 2Department of Anesthesiology, West China Hospital, Sichuan University, Chengdu, 610000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xianjie Zhang, Department of Anesthesiology, Deyang People’s hospital, No. 173 Taishan Road Section 1, Deyang, Sichuan, 618000, People’s Republic of China, Email zxianjiemazui@163.comPurpose: Lung ultrasound (LUS) is increasingly utilized in the field of anesthesiology due to its focused, quick application and the advantage of not exposing patients to ionizing radiation. This study aims to analyze the status and trends in this area from a macroscopic perspective.Methods: A bibliometric analysis was conducted using the Web of Science (WoS) Core Collection. The analysis and visualization were performed using WoS, Excel, VOSviewer, and CiteSpace. Parameters such as publications, countries, institutions, journals, and keywords were analyzed.Results: A total of 133 articles published over the last 10 years were analyzed to clarify the current status and future trends on the use of LUS in anesthesiology. The number of publications increased markedly from May 1, 2014, to April 30, 2024. China is the highest productive country, while the USA had the highest number of citations. In the institution, Seoul National University in South Korea published the most articles and had the highest number of citations. Kim Jin-Tae emerged as the most prolific and influential author. BMC Anesthesiology and the Journal of Cardiothoracic and Vascular Anesthesia were identified as the most popular journals in the field. Keywords such as “atelectasis”, “mechanical ventilation”, and “pulmonary complications” were closely related to the use of LUS in anesthesiology.Conclusion: This study provides a comprehensive analysis of research on the use of LUS in anesthesiology, highlighting the growing interest in LUS and its relevance to pulmonary complications.Keywords: lung ultrasound, anesthesiology, bibliometric analysis, mapping trends and hotspots